Pengaruh Layanan Bimbingan Kelompok Dengan Teknik Kelompok Sebaya Terhadap Konsep Diri Sosial Remaja - Widya Kartika Sari; Winda Ade Ariani (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The background of this study was the low social self-concept of adolescents in Al-Fida Orphanage Bengkulu. This research aims to determine the effect of group guidance services with peer group techniques on adolescent social self-concept. The research method used quasi-experimentation with non equivalen pre-test post-test control groups design. The study sample consisted of 20 adolescents divided into 10 expression groups and 10 control groups. Sampling techniques using purposive sampling. Data collection using self-concept questionnaires. The data were analyzed with the Mann Withney test using SPSS Version 20.0. The findings suggest that group guidance services with peer group techniques influence the social self-concept of adolescents.